2020
DOI: 10.47102/annals-acadmedsg.2020299
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in COVID-19: A Systematic Review and Meta-analysis

Abstract: Objective: Obesity has been shown to be associated with adverse outcomes in viral infections such as influenza, but previous studies on coronavirus disease 2019 (COVID-19) had mixed results. The aim of this systematic review is to investigate the relationship between COVID-19 and obesity. Methods: We performed a systematic review and meta-analysis. A literature search of MEDLINE, EMBASE, Scopus, Web of Science, CENTRAL, OpenGrey and preprint servers medRxiv and bioRxiv was performed, with no restriction on lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
80
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 55 publications
5
80
1
3
Order By: Relevance
“…None of which had been able to demonstrate utility in the treatment of COVID-19. Therefore, the efforts were focused on the development of the vaccines and so far, there are several drugs on the market that are able to relieve some of the tension placed on the healthcare system by COVID-19 [11,12]. However, while vaccination programs are widespread and the number of vaccinated patients grows, the underlying risk factors for the severe course of COVID-19 are still being investigated.…”
Section: Introductionmentioning
confidence: 99%
“…None of which had been able to demonstrate utility in the treatment of COVID-19. Therefore, the efforts were focused on the development of the vaccines and so far, there are several drugs on the market that are able to relieve some of the tension placed on the healthcare system by COVID-19 [11,12]. However, while vaccination programs are widespread and the number of vaccinated patients grows, the underlying risk factors for the severe course of COVID-19 are still being investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, one report on COVID-19 found that obesity was a more significant risk factor for hospital admission than cardiovascular disease 45 . In a recent systematic review on obesity and COVID-J o u r n a l P r e -p r o o f 19, obesity was shown to have a significant association to higher COVID-19 infection rates (OR 1.50, P<0.001), more severe COVID-19 disease (OR 3.13, 95%; P=0.005) and higher mortality (OR 1.36, 95% P = 0.006) 43 . Bariatric surgery again has an important role in managing obesity-related COVID-19 complications, with one multi-center study finding that patients who have undergone bariatric surgery 12 months or earlier developed less severe COVID-19-related symptoms than subjects who were currently obese 46 .…”
Section: Medical Benefits Of Reducing Obesity In the Covid-19 Eramentioning
confidence: 99%
“…This is especially true in light of the COVID-19 pandemic, where obesity serves as a risk factor for increased severity of symptoms from COVID-19 viral infections. Obesity was associated with increased need for hospitalization, mechanical ventilation, and increased mortality rates 43 .…”
Section: Medical Benefits Of Reducing Obesity In the Covid-19 Eramentioning
confidence: 99%
See 1 more Smart Citation
“…Пандемия COVID-19 произошла в то время, когда количество людей с избыточным весом/ожирением растет, по сути, во всех странах мира [16,17]. В настоящее время количество лиц с избыточным весом/ожирением превышает 20%, и ни в одной стране мира не отмечается тенденция к снижению числа указанных лиц [18][19][20]. Обращает внимание, что наличие сопутствующей патологии (сахарного диабета и сердечно-сосудистых заболеваний) связано с более тяжелым течением COVID-19, тогда как ожирение до сих пор практически не исследовалось.…”
unclassified